How do goats “read” 2D-images of familiar and unfamiliar conspecifics? - Langbein, Jan; Moreno-Zambrano, Mauricio; Siebert, Katrin (Frontiers in Psychology, 2023)
To study individual recognition in animals, discrimination tasks are often conducted by presenting 2D images of real conspecifics. However, animals may discriminate the images merely as visual stimulus combinations without establishing referential relationships to the individuals depicted. In the current study, we investigated whether goats are able to discriminate photos of familiar and unfamiliar conspecifics, whether they not only process the photos as visual stimuli, but also understand them as virtual copies of real conspecifics and whether they grasp the concept of familiarity. Using a computer-controlled learning device, in three tests, goats of two experimental groups (A and B) had to discriminate portrait (Te1), profile (Te2) or headless body photos (Te3) of conspecifics. Tests were presented as 4-choice tasks, with one photo from Group A (rewarded) plus three photos from Group B (distractors). That is, the rewarded photo was familiar to Group A, but unfamiliar to Group B. Finally, in a reversal test (Te4) we reversed this principle. The goats learned the discriminations in Te1 to Te3 within two days and they needed between 100 and 170 trials to reach the learning criterion, with no differences between the groups. In Te4, in contrast, the animals took 380 (B) and 390 (A) trials, respectively, to learn the task. The lack of spontaneous preferences for the photo of the familiar conspecific in the pretests of Te1 to Te3 in Group A, as well as the lack of differences in the number of trials to learn the discriminations between both groups, do not at first glance suggest that the goats established a correspondence between real conspecifics and their 2D representations. However, the higher number of trials in Te4 suggests that both groups formed the learning rule of choosing either the known (Group A) or the unknown goat (Group B) over the course of Te1 to Te3 and then failed after the rule was reversed, providing evidence that goats can associate 2D photos of conspecifics with real animals.